Fluidized bed drying of stingless bee pot-pollen: performance of swirling distributor - Luqman, Abdul Halim; Firdaus, Basrawi; Ahmmad Shukrie, Md Yudin; Siti Norazualina, Faizal (IOP Publishing, 2020)
Pot-pollen is pollen collected by stingless bees, that is mixed with honey and bee secretion, and then stored in cerumen pots. Raw pot-pollen contains high moisture content which can lead to excessive fermentation and spoilage. Drying of pot-pollen is needed to preserve them. Typically, elevated temperature can increase the drying performance. However, as pot-pollen is heat sensitive, heating above 40 °C is not preferable. Hence, the objective of this study is to investigate the drying performance of fluidized bed dryer with swirling distributor. The experiment was conducted using three different distributors, a perforated distributor, 45° and 67° swirling distributor, at 1.0 m/s and 1.5 m/s superficial air velocities. Drying experiment was conducted at ambient conditions, with no heating being applied to the pot-pollen samples. It was found that 67° swirling distributor at 1.5 m/s superficial air velocity had the highest improvement in terms of drying performance, able to reduce the moisture content from 30.5 % to 18 % within 30 minutes drying time. Hence, using swirling distributor is a suitable enhancement to fluidized bed drying especially for heat sensitive food materials.